Vagus nerve stimulation in treating depression: A tale of two stories. - Yuan, T.-F.; Li, A.; Sun, X.; Arias-Carrión, O.; Machado, S. (Current Molecular Medicine, 2016)
Vagus nerve stimulation (VNS) has been widely used to treat different neurological disorders, especially epilepsy. Accumulating evidence also suggests its potential application in antidepressive therapy, given that VNS has been confirmed by several clinical trials to exert long-term effects on mitigating depression and reducing the risk of relapse in depressed patients. Likewise, VNS has also proven to ameliorate the behavioral deficits in a rat model of depression. While the influences of VNS on monoamine metabolism and mood improvement are well-recognized, the underlying mechanisms mediating its antidepressive action remain poorly understood. Recent findings suggest that VNS-enhanced proliferation of hippocampal neural progenitor cells (NPCs) and synaptic transmission might serve as a monoamine-independent pathway contributive to the beneficial effects of VNS on depression. Here we briefly reviewed the recent progress in this field, based on which we propose that there might be, at least, two little-overlapped, and yet interactive pathways mediating the antidepressive action of VNS.
Keywords: hippocampus